2020
DOI: 10.3923/ijps.2020.432.446
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Biometric Characterization of Indigenous Guinea fowl (Numida meleagris) Populations in Northern Togo

Abstract: Objective: The present study aimed at carrying out the morpho-biometric characterization of indigenous guinea fowl populations.Materials and Methods: Data collection was conducted between March and July 2018 in two agroecological zones in northern Togo.The study was carried out on 738 adult guinea fowl. Each animal was described by direct observation. Body weight and measurements were recorded. Results: The results revealed twelve colours of the plumage with a dominance of Bonaparte (39.0%) and Pearl grey (27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Similar results were found by Kayang et al (2010) , Traoré et al (2018) and Weimann et al (2016) in guinea fowl populations of West Africa and Sudan, respectively. The higher overall rates of heterozygosity indicate a high genetic diversity, which is consistent with the great phenotypic variability observed previously in the same subpopulations ( Soara et al, 2020 ). The great genetic diversity in indigenous guinea fowl in northern Togo could be the result of the absence of selection for specific phenotype or production traits and/or uncontrolled mating in the semi-intensive rearing system, which has as consequence a continuous genes flow between populations, the conservation of a high number of alleles, and a strong heterozygosity in the populations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were found by Kayang et al (2010) , Traoré et al (2018) and Weimann et al (2016) in guinea fowl populations of West Africa and Sudan, respectively. The higher overall rates of heterozygosity indicate a high genetic diversity, which is consistent with the great phenotypic variability observed previously in the same subpopulations ( Soara et al, 2020 ). The great genetic diversity in indigenous guinea fowl in northern Togo could be the result of the absence of selection for specific phenotype or production traits and/or uncontrolled mating in the semi-intensive rearing system, which has as consequence a continuous genes flow between populations, the conservation of a high number of alleles, and a strong heterozygosity in the populations.…”
Section: Discussionsupporting
confidence: 90%
“…However, no information is available on the genetic diversity and structure of indigenous guinea fowl in Togo despite their socio-economic importance. Phenotypic characterization showed a great diversity between guinea fowl of Dry Savannah and Atakora agroecological zones on the one hand and between the different phenotypes based on the plumage colours on the other hand ( Soara et al, 2020 ). However, it did not allow the specific identification of breeds, strains or ecotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study in Ghana, Agbolosu et al [ 21 ] found that the predominant plumage colour was pearl grey colour (43.7%), whereas Traore et al [ 22 ] reported pied plumage colour (42.76%) as the most frequent colour in the provinces of Burkina Faso. The Nigerian birds shared brown eye colour (57.0%) with those of Atakora (Mountainous) dry savannah zone in Togo [ 44 ] and black shank colour with those of Kenya (95.6%) [ 16 ], Sudanian and Sudano-Guinean zones in Benin [ 45 ]. Colour polymorphism defies evolutionary expectations as a single species may maintain a striking phenotypic variation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study in Ghana, Agbolosu et al [24] found that the predominant plumage colour was pearl grey colour (43.7%), whereas Traore et al [25] reported that pied plumage colour (42.76%) was the most frequent among the provinces in Burkina Faso. The Nigerian birds shared brown eye colour (57.0%) with those of Atakora (Mountainous) dry savannah zone in Togo [50], and black shank colour with those of Kenya (95.6%) [19], Sudanian and Sudano-Guinean zones in Benin [51].…”
Section: Decision Trees Of the Data Miningmentioning
confidence: 99%